Sharī'ah issues in gold trading and gold related scam schemes - Mohd Noor, Azman (IIUM Press, International Islamic University Malaysia, 2017)
Gold trading is very common and prestigious in most of the societies.Recently, many packages or schemes that are related to gold haveappeared and developed in Malaysia, but they are subjected toquestions and disputes, as most of them are not free from riba. Ribahas been discussed extensively by Muslim scholars in thecontemporary issues of Islamic Banking and Finance area. Althoughsome types of riba are not explained clearly in the Quran, there areenormous compilations of hadith that detail out the occurrence ofriba in the trading of the ribawi items, including gold. This paperwill discuss the issues of riba, which arise from gold trading as wellas gold related scam schemes. The research method used in thispaper is by explaining how riba takes place in gold trading withdeferment (riba al-nasi’ah), arguments to allow the deferment andrefutations and some models of gold scam schemes. The majoroutcomes of the paper is to expose to the public the permissible wayof gold trading, tricks used by gold scammers, the models of theprogram, riba issue and other related Shari’ah issue.